Influence of SiC particle size and drying method on mechanical properties and microstructure of Si3N4/SiC nanocomposite - Hwang, KT; Kim, CS; Auh, KH; Cheong, DS; Niihara, K (ELSEVIER SCIENCE BV, 1997)
Si3N4/20 vol% SiC nanocomposites with different SiC particle sizes (mean particle size of 30 nm and 270 nm, which were made by plasma CVD and carbothermal reduction, respectively) were fabricated by hot pressing. The effects of second-phase particle size and drying methods for mixed slurry (microwave drying and rotary evaporator) on microstructure and mechanical properties were analyzed. The nanocomposite with ultra-fine (30 nm) SiC dispersoid had a high average strength of 1680 MPa. This value was 26% higher than that of the nanocomposite with coarser (270 nm) SiC dispersoid and corresponded to the strength of nanocomposite made from amorphous Si-C-N precursor powder. Fracture strength and microstructure of the nanocomposite were significantly influenced by the drying methods as well as the SiC particle size, Refinement of microstructure and deagglomoration of the SiC particles were the main reasons for strengthening of the nanocomposite. Furthermore, consolidation of grain boundary phase caused by free-carbon impurity in ultra-fine SiC powder could also be an important factor in the improvement of strength.
Keywords: HOT-PRESSED SI3N4; TEMPERATURE FAILURE MECHANISMS; SILICON-NITRIDE COMPOSITES; STRENGTH; CERAMICS; FRACTURE; BEHAVIOR; GROWTH; PHASE